Phytoplankton σPSII and Excitation Dissipation; Implications for Estimates of Primary Productivity - Xu, Kui; Lavaud, Johann; Perkins, Rupert; Austen, Emily; Bonnanfant, Marlène; Campbell, Douglas A. (Frontiers in Marine Science, 2018)
The effective absorption cross section for photochemistry of Photosystem II in the light (σPSII′) comprises the probability of light capture by Photosystem II and the quantum yield for subsequent photochemistry. σPSII′ is used to model photosynthesis and aquatic productivity. Phytoplankters regulate σPSII′ to mitigate over- or under-excitation of Photosystem II. We used diverse phytoplankton taxa to compare short term changes in σPSII′ with the induction of the yield of non-photochemical quenching (YNPQ) of chlorophyll fluorescence, a measure of regulated excitation dissipation. In two picocyanobacteria σPSIIʹ showed no decline upon induction of moderate YNPQ, above light levels sufficient for saturation of electron transport. In the eukaryotic chl a/b Ostreococcus and the chl a/c diatom Thalassiosira, induction of non-photochemical quenching was stronger after growth under saturating light, an acclimation attributable to increased xanthophyll cycle pigment content. Across short and longer-term light histories to induce or relax regulatory processes Ostreococcus and Thalassiosira showed proportional variations between the level of YNPQ and the down regulation of σPSIIʹ. The proportional down regulation of σPSIIʹ was, however, significantly smaller than the amplitude of YNPQ induction. For the eukaryotes we can predict changes in σPSIIʹ, useful for modelling electron transport, productivity and acclimation, from measures of YNPQ, which are accessible from fluorescence yield measures that do not include σPSII′. This useful relation, however, does not extend to the tested prokaryotes, possibly as a result of differential violations of the rate constant assumptions that underlie the calculated YNPQ parameter.